Nomina Inserere Voluerint, Non Prohibeatur. Nominal Inscriptions Inside the Altar in the North-East of the Iberic Peninsula (9th-13th Centuries) (Fenestella. Inside Medieval Art, 2022)
Some manuscripts of the 11th and 12th centuries preserved in Catalonia present a specific rite when a bishop had to consecrate a church. In the altar he placed relics, three fragments of hosts, three grains of incense and small parchments on which was written the information about the consecration, the ten commandments and the beginning of the four gospels. The Catalan consecration ritual corresponded to a specific liturgical codification, the Catalan-Narbonne ordo, which is generally accepted to have been strictly followed. However, archaeological excavations carried out in pre-Romanesque and Romanesque churches in Catalonia since the 19th century have often brought to light a practice that was not codified in these texts: the modest containers of wood, stone or alabaster that contained the consecration relics had been engraved with names. This paper is dedicated to these nominal inscriptions from the consecration ritual, found inside the altars.
Keywords: Medieval epigraphy; Consecration; Nominal inscription; Altar; Lipsanoteca